Benefits of a Short-Term Obesity Reduction Intervention Among Obese Older Adults with Prediabetes: Preliminary Evidence by Race (Black/White) from the EGGSPDITe Study. (29th May 2020) - Miller, Marshall; Borack, Michael; Rincker, Jamie; McDonald, Shelley; Starr, Kathryn Porter; Bales, Connie
Abstract: Objectives: Obesity rates in older adults are rapidly climbing, especially in older African Americans, for whom it hastens functional decline and intensifies chronic health conditions like Type 2 diabetes more so than in their white counterparts. Emerging evidence suggest that increased protein intake can enhance the benefits of intentional weight loss but it is not yet known whether these effects are consistent across race. Methods: The ongoing EGGSPDITe trial assess the effects of combining generous intakes of high quality animal protein (≥30 g/meal; primarily from eggs) with calorie restriction, relative to calorie restricted alone, on insulin resistance and weight loss among black and white older adults with prediabetes who are participating in this 4-month obesity reduction intervention. Results: Preliminary combined-group analysis reveals significant reductions in body weight (–9.7 ± 7.6 kg), body fat (–8.1 ± 7.6 kg), and HbA1c (–0.2 ± 0.3%) and significant improvement in SF-36 physical and mental health composites (+10.8 and + 4.8, respectively; P s < 0.01) at 4 months, relative to baseline. Significant improvements in 6-minute walk distance and 8-foot up and go ( P s ≤ 0.05) at 4 months; however, a significant race x time interaction ( P < 0.05) reveals that improvements in 30-second chair stands improved among white but not black participants (+2.4 vs 0.4 stands, respectively). No other significant differences were observed between older black and white pre-diabetics. Conclusions: These preliminary findings suggest that even short-term obesity reduction intervention can improve the body composition, metabolism, and self-reported health of obese older adults with prediabetes but responses may vary by race for some outcomes. Funding Sources: This study was funded by the National Institute on Aging and the Egg Nutrition Council.